2021
DOI: 10.1021/acs.organomet.1c00283
|View full text |Cite
|
Sign up to set email alerts
|

Syn-Insertion of Alkynes into Gold–Phosphito Bonds: Stereoselectivity and Reversible Protodeauration

Abstract: The susceptibility of gold phosphito compounds to undergo alkyne insertion into gold–phosphorus bonds has been investigated. An electron-deficient alkyne (DMAD) underwent syn-insertion into the gold–phosphorus bond to generate a Z-vinylgold species, whereas electron-rich internal alkynes were unreactive. When a P-chiral phosphinate was used as a probe, the protodeauration and insertion steps were found to be stereospecific. In contrast to the insertion chemistry observed with DMAD, electron-deficient terminal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 78 publications
(145 reference statements)
0
1
0
Order By: Relevance
“…Homogeneous gold catalysis has emerged as an important topic for the efficient construction of complex molecular architecture. In general, these reactions are triggered by the nucleophilic attack on the gold-coordinated C–C multiple bonds to form an organo-gold intermediate that upon protodemetalation delivers the product. On the contrary, the development of Au­(I)-catalyzed cross-coupling reactions seems to be quite challenging because unlike its isoelectronic counterpart Pd(0), Au­(I) does not change its oxidation state during the catalytic cycle. This apparent reluctance to engage in redox activity is commonly attributed to the comparatively high redox potential of the Au­(I)/Au­(III) couple ( E ° = +1.41 V) to the Pd(0)/Pd­(II) couple ( E ° = +0.92 V) . Therefore, the oxidative addition of organic halides or equivalents ubiquitous in palladium/nickel-catalyzed reactions rendered nontrivial for Au­(I) for many decades. However, recent research articles have revealed the use of strong oxidizing or fluorinating agents like (diacetoxyiodo)­benzene, Selectfluor, N -fluorobenzenesulfonimide, ArN 2 X, P–N ligand, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Homogeneous gold catalysis has emerged as an important topic for the efficient construction of complex molecular architecture. In general, these reactions are triggered by the nucleophilic attack on the gold-coordinated C–C multiple bonds to form an organo-gold intermediate that upon protodemetalation delivers the product. On the contrary, the development of Au­(I)-catalyzed cross-coupling reactions seems to be quite challenging because unlike its isoelectronic counterpart Pd(0), Au­(I) does not change its oxidation state during the catalytic cycle. This apparent reluctance to engage in redox activity is commonly attributed to the comparatively high redox potential of the Au­(I)/Au­(III) couple ( E ° = +1.41 V) to the Pd(0)/Pd­(II) couple ( E ° = +0.92 V) . Therefore, the oxidative addition of organic halides or equivalents ubiquitous in palladium/nickel-catalyzed reactions rendered nontrivial for Au­(I) for many decades. However, recent research articles have revealed the use of strong oxidizing or fluorinating agents like (diacetoxyiodo)­benzene, Selectfluor, N -fluorobenzenesulfonimide, ArN 2 X, P–N ligand, etc.…”
Section: Introductionmentioning
confidence: 99%